2021
DOI: 10.1016/j.ejca.2021.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Clinical practice guideline for the prevention of oral and oropharyngeal mucositis in pediatric cancer and hematopoietic stem cell transplant patients: 2021 update

Abstract: To update the 2015 clinical practice guideline for the prevention of oral mucositis in pediatric cancer or hematopoietic stem cell transplant (HSCT) patients. Methods: We performed seven systematic reviews of mucositis prevention. Three reviews included randomized controlled trials (RCTs) conducted in pediatric and adult patients evaluating cryotherapy, keratinocyte growth factor (KGF) or photobiomodulation therapy with a focus on efficacy. Three reviews included studies of any design conducted in pediatric pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 26 publications
(17 reference statements)
1
28
0
3
Order By: Relevance
“…The study settings ranged from case series, cohort studies, and non-randomized trials to RCTs. The results are promising as demonstrated in the meta-analysis by Patel et al in 2021 (97). They showed that PBM could significantly reduce the incidence of severe OM in pediatric patients based on 16 studies.…”
Section: Acute Oral Mucositismentioning
confidence: 92%
See 1 more Smart Citation
“…The study settings ranged from case series, cohort studies, and non-randomized trials to RCTs. The results are promising as demonstrated in the meta-analysis by Patel et al in 2021 (97). They showed that PBM could significantly reduce the incidence of severe OM in pediatric patients based on 16 studies.…”
Section: Acute Oral Mucositismentioning
confidence: 92%
“…They showed that PBM could significantly reduce the incidence of severe OM in pediatric patients based on 16 studies. However, due to significant differences in PBM protocols in these trials (as IN the MASCC/ISOO analysis), it is hard to make definite recommendations for pediatric patients at the moment (97)(98)(99)(100). Nonetheless, these studies emphasize the non-invasive, patient-friendly, safe and well-tolerated therapy PBM represents.…”
Section: Acute Oral Mucositismentioning
confidence: 99%
“…A recent application of NHSN criteria in pediatric hospitals in the United States demonstrated that MBI accounted for 40% of CLABSI in immunocompromised pediatric patients, which replicates the findings in our study ( 11 ). While strategies to decrease mucositis, such as oral rinses, cryotherapy, and low level light therapy have been recommended in high resource settings, this will not prevent all MBI ( 12 ). Moreover, the feasibility of implementation and the cost vs. benefit of interventions will have to be evaluated within the local context.…”
Section: Discussionmentioning
confidence: 99%
“…8 Nevertheless, cryotherapy was previously indicated to be performed only on older and cooperative pediatric patients. 9 Honey has attracted the attention of medical care in the past decades because of its tissue healing, antibacterial and antioxidant properties, 10 and has been shown to be an acceptable traditional medicine (Natural Product) globally. 11 Based on the present knowledge, honey is efficiently used to treat chemotherapy-induced OM.…”
Section: Introductionmentioning
confidence: 99%